potrzebuje na szybko ​



Potrzebuje Na Szybko class=

Odpowiedź :

1)

f(x) = x² - x - 2

x² - x - 2 = 0

a = 1, b = -1, c = -2

∆ = (-1)² - 4 * 1 * (-2) = 1 + 8 = 9

√∆ = √9 = 3

x = (-(-1) - 3)/2 = (1 - 3)/2 = -2/2 = -1

x = (-(-1) + 3)/2 = (1 + 3)/2 = 4/2 = 2

2)

f(x) = x² - 10x + 25

x² - 10x + 25 = 0

(x - 5)² = 0

x - 5 = 0

x = 5

3)

f(x) = 4x² - 3x + 6

4x² - 3x + 6 = 0

a = 4, b = -3, c = 6

∆ = (-3)² - 4 * 4 * 6 = 9 - 96 = -87

∆ < 0, brak rozwiązań

4)

f(x) = 3x² - 6x

3x² - 6x = 0 / : 3

x² - 2x = 0

x(x - 2) = 0

x = 0 lub x = 2

Odpowiedzi na zdjęciach :)

Zobacz obrazek Julafrania
Zobacz obrazek Julafrania